2021
DOI: 10.1002/cam4.4461
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors to predict the survival in patients with advanced gastric cancer who receive later‐line nivolumab monotherapy—The Asahikawa Gastric Cancer Cohort Study (AGCC)

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 32 publications
0
11
1
Order By: Relevance
“…Although the differentiated histological type is an advantage of AGC ( 52 ), this case was a poorly differentiated adenocarcinoma with a good response to nivolumab. Distinct from our case, previous studies have suggested that HER-2 -positive status is related to the improvement of prognosis ( 18 , 53 ). Furthermore, some studies have proposed that the co-expression of HER-2 and PD-L1 may contribute to the immune escape of GC, meaning that HER-2 -negative status creates favorable conditions for effective immunotherapy ( 12 ).…”
Section: Discussioncontrasting
confidence: 80%
See 2 more Smart Citations
“…Although the differentiated histological type is an advantage of AGC ( 52 ), this case was a poorly differentiated adenocarcinoma with a good response to nivolumab. Distinct from our case, previous studies have suggested that HER-2 -positive status is related to the improvement of prognosis ( 18 , 53 ). Furthermore, some studies have proposed that the co-expression of HER-2 and PD-L1 may contribute to the immune escape of GC, meaning that HER-2 -negative status creates favorable conditions for effective immunotherapy ( 12 ).…”
Section: Discussioncontrasting
confidence: 80%
“…The significant anti-tumor effect, low response rate, and high incidence of immune-related adverse events (IRAEs) of nivolumab make its applicable conditions and optimal withdrawal time controversial ( 16 18 ). The ATTRACTION-2 trial has shown that the complete response rate was only 1.1% in the overall population, and 50% of the patients exhibited early disease progression.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For unresectable ESCC in the immunotherapy era, a traditional TNM staging system was inadequate for directing the treatment protocols. The nomogram, a visual representation of a multiple regression analysis model, has been widely used in tumor prognostic analysis [ 54 , 55 ]. As a statistical tool, it could provide a tailored risk prediction, as well as compute individual predicted survival probabilities at different time points.…”
Section: Discussionmentioning
confidence: 99%
“…The significant anti-tumor effect, low response rate, and high incidence of immune-related adverse events (IRAEs) of nivolumab make its applicable conditions and optimal withdrawal time controversial (16)(17)(18). The ATTRACTION-2 trial has shown that the complete response rate was only 1.1% in the overall population, and 50% of the patients exhibited early disease progression.…”
Section: Introductionmentioning
confidence: 99%